Caffeinated instant coffee prevents an increase in exercise-mediated superoxide anion production in rat peritoneal neutrophils - Elisson Meireles Lamim Jerônimo; André Luiz Machado Viana; Miriam das Dores Mendes Fonseca; Marilene Lopes Ângelo; Bruno Cesar Correa Salles; Stella Maris da Silveira Duarte; Sônia Aparecida Figueiredo; Maria Rita Rodrigues; Fernanda Borges de Araujo Paula (São Paulo State University (UNESP), 2020)
The present study analyzed the in vivo effects of drinking caffeinated and decaffeinated instant coffee (8% w/v) by adult male Wistar rats submitted to high-intensity exercises. The parameters used in the evaluation were the determination of the activities of NADPH oxidase, myeloperoxidase and other antioxidant enzymes present in neutrophils of rats. It was observed that exercise-induced superoxide anion production depends on the NADPH oxidase activity (estimated by the cytochrome C reduction test) in peritoneal neutrophils (p < 0.05). The intake of caffeinated and decaffeinated instant coffee beverages and of a caffeine solution to 1.67% did not induced changes in myeloperoxidase, superoxide dismutase and glutathione peroxidase activities in the peritoneal neutrophils of rats after exercise (p < 0.05). From the obtained results, it was concluded that moderate intake of caffeinated instant coffee (equivalent to a daily human consumption of 4 50-mL cups of coffee) may have beneficial effects on health, contributing to a reduction in superoxide anion generation triggered in neutrophils after high-intensity exercise.